(untitled) (Global Media Journal - German Edition, 2023)
This paper discusses how television professionals in Germany negotiate the transnational potential as well as the regional, national and local particularities of German quality drama. The central hypothesis is that the practitioners’ current industry discourse on quality TV drama bears clear “glocal” traits, as their debates on transnationalisation focus on national or local specificities as well. Drawing on the theoretical concept of glocalisation, the analysis is based on 12 expert interviews with 15 producers, scriptwriters, commissioning editors and directors of recent quality TV drama projects from Germany. First, the article outlines key concepts and methods for the analysis. Subsequently, it describes transnationalism and regionalism in the German-speaking television landscape and among public broadcasters, which are the most important commissioners of German TV fiction. Further, the article deals with industry discourses on foreign sales and transnational distribution. Finally, it discusses the transnationalisation of project networks and individual practitioners on a micro level.